Effects of pores on the superelasticity coupled with plasticity in nanocrystalline NiTi shape memory alloys: A molecular dynamic study - Xiang Zhu; Chenyan Liu; Yaguang Wang; Guansuo Dui (Journal of Materials Research and Technology)
Nanocrystalline NiTi SMAs combine the advantages of shape memory materials and nanocrystalline metals, with their mechanical properties being highly sensitive to the presence of pores. However, the influence mechanisms of pore characteristics (including quantity, shape, orientation, and spatial distribution) on the superelasticity and plasticity of nanocrystalline NiTi SMAs remain unclear. This study employs molecular dynamics simulations to systematically investigate the role of pore characteristics in the superelastic and plastic responses of nanocrystalline NiTi SMAs. The increase in pore quantity exerts non-monotonic effects on martensitic transformation and the formation and propagation of dislocation. Elongated pores along the loading direction promote a more uniform stress distribution, alleviating local stress concentration and enhancing phase transformation and peak stresses. Notably, the patterns of pore distribution alter stress transmission paths and stress fields, thereby influencing martensitic transformation, dislocation evolution, disordered structure formation, and residual martensite content. These findings reveal the influence of pore characteristics on the microstructure, superelasticity, and superelastic-plasticity of nanocrystalline NiTi, laying the foundation for its application in precision engineering fields such as biomedical implants and microelectromechanical systems. In particular, the study of pore distribution can provide guidance for optimizing the mechanical properties of porous NiTi scaffolds.